Serum β2-MG, sCHE, and PSGL-1 Expression in Patients with Esophageal Cancer and Their Association with Postoperative Lung Infection After Mediastinoscopy - Yu FENG; Rulin QIAN; Dong CUI; Chaoying CHANG; Maolin CHEN (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate serum β2-MG, sCHE, and PSGL-1 expression in patients with esophageal cancer and their relationship to lung infection after mediastinoscopy. MethodsA total of 118 patients with esophageal cancer were selected and divided into infected and uninfected groups according to whether they developed lung infection after surgery. An automatic microbiological identification system was used to detect the pathogenic bacteria of lung infection. ELISA was used to detect the levels of β2-MG, sCHE, and PSGL-1. Multivariate logistic regression was used to analyze the influencing factors of postoperative lung infection in patients with esophageal cancer. ROC curves were plotted to analyze the assessment value of serum β2-MG, sCHE, and PSGL-1 on postoperative lung infection. ResultsFifty-two strains of bacteria were isolated from the sputum of 38 patients with postoperative lung infections, and these included 35 (67.31%) Gram-negative, 14 (26.92%) Gram-positive, and 3 (5.77%) fungal strains. The difference in long-term smoking history between the infected and uninfected groups was statistically significant (P<0.05). Serum β2-MG and PSGL-1 levels were significantly higher and sCHE levels were significantly lower in the infected group than in the uninfected group (P<0.05). Serum β2-MG and PSGL-1 levels were sequentially higher (P<0.05) and sCHE levels were sequentially lower (P<0.05) in the mild, moderate, and severe lung infection groups. Long-term smoking history, β2-MG, and PSGL-1 were risk factors affecting postoperative lung infection in patients with esophageal cancer (P<0.05), and sCHE was a protective factor (P<0.05). The AUCs of serum β2-MG, sCHE, and PSGL-1 for assessing postoperative lung infections were 0.807, 0.845, and 0.800, respectively, and the AUC of the three combined factors for assessing postoperative lung infections was 0.954, which was superior to that assessed individually (Zcombination vs. β2-MG=2.576, Zcombination vs. sCHE=2.623, Zcombination vs. PSGL-1=2.574, all P<0.05). ConclusionThe serum levels of β2-MG and PSGL-1 increase and the sCHE level decreases in patients with esophageal cancer and postoperative pulmonary infection, which are also related with lung infection. Combined testing can improve the evaluation value of postoperative pulmonary infection in patients.